The influence of Digital Literacy and Learning Independence on Learning Outcomes in Statistics Courses - Setyaedhi, Hari Sugiharto; Pramana, Atan (Universitas Pendidikan Ganesha, 2025)
The problem in this study is the low utilization of digital literacy and learning independence by students, which has an impact on the learning outcomes of statistics courses that are below standard. This study aims to analyze the influence of digital literacy on statistical learning outcomes, the influence of learning independence on statistics learning outcomes, and the influence of digital literacy and learning independence simultaneously on statistical learning outcomes. This type of research is ex-post facto with research subjects of 90 students in the Department of Educational Technology. The data collection technique used questionnaires to measure the variables of digital literacy and learning independence, while learning outcome data was obtained from statistics course scores. Data analysis was carried out using multiple linear regression with analysis prerequisite tests including normality, linearity, multicollinearity, and heteroscedasticity tests. The results showed that digital literacy had a significant effect on statistical learning outcomes with a significance value of 0.00 < 0.05 and a contribution of 73.5% (R²), learning independence also had a significant effect on statistical learning outcomes with a significance value of 0.00 < 0.05 and a contribution of 48.6% (R²), and simultaneously digital literacy and learning independence had a significant effect on statistical learning outcomes with a significance value of 0.00 < 0.05 and contribution of 75.7% (R²). The conclusion of this study is that digital literacy and learning independence have a significant effect both partially and simultaneously on student learning outcomes. The implications of this study show the importance of strengthening digital literacy and learning independence in an effort to improve students' academic achievement, especially in statistics courses.